Pengaruh Disiplin Kerja dan Komitmen Organisasi Terhadap Produktivitas Kerja Karyawan Departemen Produksi Pada PT X - Destyana Rahmah, Anggi; Wahyu Handaru, Agung; Sholikhah, Sholikhah (SINOMIKA Journal: Publikasi Ilmiah Bidang Ekonomi dan Akuntansi, 2023)
This study has the objectives, namely: (1) to determine the effect of work discipline on the work productivity of the employee of the production department of PT X, (2) to determine the effect of organizational commitment on the work productivity of the employee of the production department of PT X, (3) to determine the effect of work discipline and commitment organization on the work productivity of the employee of the production department of PT X together. The research method uses quantitative methods with a descriptive approach. The sample used in this study amounted to 109 employees with sampling using the Slovin formula and using the simple random sampling technique. The data analysis technique used in research is multiple linear regression analysis. Based on the results of the study shows that: work discipline has a positive and significant influence on work productivity, organizational commitment has a positive and significant influence on work productivity, and work discipline and organizational commitment have a positive and significant influence on work productivity.